Analysis of residual perinatal transmission of hepatitis B virus (HBV) and of genetic variants in human immunodeficiency virus and HBV co-infected women and their offspring - Khamduang W. (2014)
Background: Despite implementation of universal infant hepatitis B (HB) vaccination, mother-to-child transmission (MTCT) of hepatitis B virus (HBV) still occurs. Limited data are available on the residual MTCT of HBV in human immunodeficiency virus (HIV)-HBV co-infected women. Objectives: We assessed the prevalence of HBV infection among HIV-infected pregnant women and the rate of residual MTCT of HBV from HIV-HBV co-infected women and analyzed the viral determinants in mothers and their HBV-infected children. Study design: HIV-1 infected pregnant women enrolled in two nationwide perinatal HIV prevention trials in Thailand were screened for HB surface antigen (HBsAg) and tested for HBeAg and HBV DNA load. Infants born to HBsAg-positive women had HBsAg and HBV DNA tested at 4-6 months. HBV diversity within each HBV-infected mother-infant pair was analyzed by direct sequencing of amplified HBsAg-encoding gene and cloning of amplified products. Results: Among 3312 HIV-1 infected pregnant women, 245 (7.4%) were HBsAg-positive, of whom 125 were HBeAg-positive. Of 230 evaluable infants born to HBsAg-positive women, 11 (4.8%) were found HBsAg and HBV DNA positive at 4-6 months; 8 were born to HBeAg-positive mothers. HBV genetic analysis was performed in 9 mother-infant pairs and showed that 5 infants were infected with maternal HBV variants harboring mutations within the HBsAg "a" determinant, and four were infected with wild-type HBV present in highly viremic mothers. Conclusions: HBV-MTCT still occurs when women have high HBV DNA load and/or are infected with HBV variants. Additional interventions targeting highly viremic women are thus needed to reduce further HBV-MTCT. © 2013 Elsevier B.V.